Pengenalan Aksara Batak Dengan Metode Perceptron - Frinto Tambunan (STIKOM Tunas Bangsa Pematangsiantar, 2019)
Water is a good solvent, so that the water in nature is never pure. If the content of various substances and microorganisms contained in water exceeds the allowable threshold, the water quality will be compromised. Impaired water quality is said to be contaminated water. With so keep in mind how the level of contamination found in the water. With the construction of an artificial neural network using the Perceptron network is expected to be built capable of providing the level of water pollution prediction results.